Choroid plexus dysfunction: The initial event in the pathogenesis of Wernicke's encephalopathy and ethanol intoxication - Nixon, P.; Jordan, L.; Zimitat, Craig; Rose, S.; Zelaya, F. (Wiley-Blackwell Publishing, Inc., 2008)
Background: In both acute ethanol intoxication and in thiamin deficient glucose metabolism, previous studies have detected blood-brain barrier (BBB) and/or blood-CSF-barrier (BCSFB) impairment but were unable to assess their significance in relation to other changes in the brain. Methods: Contrast-enhanced, magnetic resonance imaging (MRI) was used to detect and time any impairment of the BBB or BCSFB in rats given an acute ethanol load or in rats made thiamin deficient to the point of mild ataxia and then given an acute glucose load. Results: The BCSFB at the choroid plexus (CP) was impaired within 10 minutes by either (i) a single i.p. dose of glucose in thiamin-deficiency, an effect that was attenuated by prior MK801 and preceded the published onset of exacerbation of motor incoordination and elevation of brain glutamate derivatives; or (ii) a single i.p. dose of ethanol in thiamin-sufficiency, an effect that was proportional to the blood alcohol concentration and preceded the published onset of signs of intoxication. In contrast to the BCSFB, the BBB remained intact throughout the 90 minutes period of these experiments. Conclusions: In both ethanol intoxication and thiamin-deficient glucose metabolism, BCSFB impairment exposes the CSF and hence the brain extracellular fluid to neuroactive substances from the blood. CP impairment is the earliest detected event in both these animal models; and explains the paraventricular location of WE neuropathology and why WE is associated with, but not dependent on, alcoholism. Copyright © 2008 by the Research Society on Alcoholism.